Development of an IoT System with Smart Charging Current Control for Electric Vehicles - Ferreira, J.; Nogueiras Melendez, A. A. (IECON 2018 - 44th Annual Conference of the IEEE Industrial Electronics Society, 2018)
This paper presents the development and test of an Internet of Things (IoT) system for monitoring and control of electric vehicles. The IoT architecture, which was developed using the Firebase platform, allows the synchronization of the vehicles' data to the online server, as well as the access to the data outside of the vehicle, though the Internet. The smart charging system proposed in this paper allows the control of the electric vehicle's battery charging current in real time, based on the demand at the residence (home current), which is measured using a residential wireless sensor network (WSN). An Android mobile app was developed to access the vehicle's data. This app communicates with the wireless sensor nodes of an intra-vehicular wireless sensor network (IVWSN), which was developed using the Bluetooth Low Energy (BLE) protocol. A real time notification system was also implemented to alert users about certain events, such as low battery and full battery charge. The main features of the proposed IoT system are validated through experimental results.